2001
DOI: 10.1063/1.1377031
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry principles in the nuclear magnetic resonance of spinning solids: Heteronuclear recoupling by generalized Hartmann–Hahn sequences

Abstract: General symmetry principles for rotor-synchronized pulse sequences in magic-angle spinning solid-state nuclear magnetic resonance are presented. The theory of symmetry-based pulse sequences using pulse elements is presented for the first time. The symmetry theory is extended to the case of generalized Hartmann-Hahn sequences, in which rotor-synchronized rf irradiation is applied simultaneously to two isotopic spin species. The symmetry principles lead to heteronuclear selection rules. The symmetry theory is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
231
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 217 publications
(232 citation statements)
references
References 84 publications
1
231
0
Order By: Relevance
“…There are many different types of pulse sequences achieving recoupling of heteronuclear dipolar couplings. [28][29][30] A detailed overview of the different properties of a selection of heteronuclear recoupling sequences can be found in ref 31. In the following, the most prominent sequences are briefly presented and discussed in the context of estimating 17 O-1 H heteronuclear dipolar couplings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different types of pulse sequences achieving recoupling of heteronuclear dipolar couplings. [28][29][30] A detailed overview of the different properties of a selection of heteronuclear recoupling sequences can be found in ref 31. In the following, the most prominent sequences are briefly presented and discussed in the context of estimating 17 O-1 H heteronuclear dipolar couplings.…”
Section: Introductionmentioning
confidence: 99%
“…These sequences achieve heteronuclear longitudinal two-spin-order (I z S z ) recoupling, hence not suffering from dipolar truncation, while decoupling the I-spin homonuclear dipolar couplings. 31,30 The heteronuclear longitudinal two-spin-order recoupling sequences are demonstrated by numerical simulations and by experimentally estimating the 17 In this contribution we combine the approaches described above to develop a comprehensive methodology to study hydrogen bonding in biological systems through 17 O and 17 O-1 H NMR.…”
Section: Introductionmentioning
confidence: 99%
“…45, 60 it is shown that these symmetry properties lead to selection rules on the average Hamiltonian terms:…”
Section: First-order Selection Rulesmentioning
confidence: 99%
“…45,60 A summary of the spin interaction components, in the case of exact magic-angle spinning, is given in Table 2.…”
Section: Rotational Componentsmentioning
confidence: 99%
See 1 more Smart Citation